Ultrasound-guided intraoperative electron beam radiation therapy: A phantom study. (October 2020) - Ma, Pan; Li, Minghui; Chen, Xinyuan; Tian, Yuan; Niu, Chuanmeng; Feng, Qinfu; Dai, Jianrong
Highlights: The ultrasound-guided intra-operative radiation therapy method was established. The intra-operative 3D dose distribution could be provided. The compensator may be an alternative to deliver intra-operative radiation therapy. Abstract: Purpose: To develop the method for ultrasound (US)-guided intra-operative electron beam radiation therapy (IOERT). Methods: We first established the simulation, planning, and delivery methods for US-guided IOERT and constructed appropriate hardware (the multi-function applicator, accessories, and US phantom). We tested our US-guided IOERT method using this hardware and the Monte Carlo simulation IOERT treatment planning system (TPS). The IOERT TPS used a compensator to build the conformal dose distribution. Then, we used the TPS to evaluate the effect of setup uncertainty on target coverage by introducing phantom setup error ranging from 0 mm to 10 mm to the plans with and without the compensator. Results: The simulation, planning, and delivery methods for US-guided IOERT were introduced and validated on a phantom. A complete technique for US-guided IOERT was established. Target coverage decreased by about 12% and 29% as the phantom setup error increased to 5 mm and 10 mm for the plans with compensator, respectively. Without compensator, the corresponding target coverage decreases were 2% and 13%, respectively. Conclusion: In our study, we developed the multi-function applicator, US Phantom, and TPS for IOERT. The procedures included not only dose distribution planning, but also intraoperative US imaging, which provided the information necessary during surgery to improve IOERT quality assurance. Target coverage was more sensitive to setup errors with compensator compared to no compensator. Further studies are needed to validate the clinical efficacy of this US-guided IOERT method.